Design optimization of vertical axis wind turbine on Malaysia sea - Ahmad Aiman Muhamad Ismail (2023)
The main goals of this project is to design highly efficient wind turbine that can operate at low wind speed condition and to design the rotor housing that can increase significant value towards efficiency of Vertical Axis Wind Turbine, VAWT. The scope of this project includes the research and study of previous work circling around the design optimization of VAWT and Rotor Housing, RH through journal article, website, and conferences and my more. Then, it is followed by proposing solution for design optimization problem through simulation analysis. Then the third scope of work will be collecting and studying the results obtained from the simulation. The rationale to pursue this project is studies on wind energy in Malaysia was poorly concentrated on VAWT, which have high potential in low average wind speed’s country. For methodology part, the methods used is by using Computational Fluid Dynamic to perform the fluid simulation. The process includes having 3D design created using SOLIDWORKS and applying CFX flow analysis inside the ANSYS software. Some of the starting point to create the designs were from previous interpreted from previous studies such as number of turbine blades, the tip speed ratio and angle of deflector for RH. New findings in this project includes aspect ratio of VAWT’s blades should be around 1.33, shape of turbine blades is better as horizontal axis blades, outlet area of RH concentrators are best as it become much smaller than the inlet and ratio of RH is best at 1.8 or better.